Mass Customization based on additive manufacturing: technology selection, elicitation loop, and distributed production on a tailored customization experiment - Durão, Luiz Fernando Cardoso dos Santos (2017)
Product customization is a competitive advantage in several industry sectors; however, it has posed a significant challenge for the industry. In many cases, higher levels of product individualization result in increased complexity to manage individual customer information and lead to reduced scale cost advantages. Existing initiatives in product customization are mainly focused on the product assembly stage of predefined variants, without changing product design or geometry. Recent information management and flexible manufacturing technologies in a connected environment can support advances in current customization approaches and levels. To create a connected environment in manufacturing, components must be able to store and exchange data with machines, and with other components and assemblies of the entire production system. At the same time, Smart Product features require that products and components be able to store and exchange data throughout their entire lifecycle. The integration of modern Internet technologies enables distributed production using Additive Manufacturing (AM) on a global scale and conditioning monitoring of machines and processes. The manufacturing of products distributed in locations closer to the final usage point may have several advantages, such as reduced logistics costs and reduced inventory levels over the supply chain. In this work, Product Lifecycle Management (PLM) and Additive Manufacturing (AM) are combined to build a customization scenario including geometry-based customization for individual customer requirements. Besides, distributed manufacturing is used to reduce the costs of the supply chain. The aim of the work is to demonstrate the design and implementation of distributed manufacturing scenario for tailored, customized products based on Industrie 4.0\'s - fourth industrial revolution - concepts and AM technologies. Research results include detailed customization process, information flow mapping, and the technology required to manage a distributed manufacturing. Besides, it shows that the combination of MC, AM and distributed manufacturing leads to a paradigm shift in enterprise networks.